Analysis of Power and Voltage Losses in Electric Submersible Pump Motor Installations - Habib, Khusnul Habib Siregar; Azhari zakri, Azriyenni (International Journal of Electrical, Energy and Power System Engineering, 2024)
In area mining are quite extreme, where the level of safety from high temperatures and toxic gases which are explosive as well as well flow pressure is also high and can damage production equipment. Therefore, it is very necessary to install reliable electrical power, starting from analyzing the selection of cable types that used, voltage drop, power losses and transformer selection. The problems mentioned previously, this research carried out an analysis of improvements to voltage drops and power losses that occurred in the ESP motor installation system. The method used is to replace the type of cable used in three scenarios with three different types of cable. The installation system data obtained from this company was then processed using software which was then validated with theoretical calculation results. The result of voltage drops and power losses in ESP cables according to standards using scenario 3, replacing AWG 2/0 type with a voltage rating of 5 kV, diameter of 11.709 mm and has a KHA of up to 210 A. The voltage drop value after repairs are carried out based on theoretical calculation results has an average percentage index value of 4.5% and power losses of 4.6%. This shows that in the condition after repairs, both the results of simulation calculations and theoretical values have met the IEEE std 141-1993 standard which states that the value of voltage drop and power losses in industrial plan distribution systems must be below 5%.